Inflation Led Import or Import Led Inflation: Evidence from Bangladesh - Muktadir-Al-Mukit, Dewan; Shafiullah, A. Z. M.; Ahmed, Md. Rizvy (Asian Business Review, 2013)
This study investigates the relationship between inflation and import for the economy of Bangladesh over the sample period of 2000 to 2011. This study used different econometric techniques of measuring the long and short term relationship between     variables. The Johansen Cointegration test is used to determine the existence of a long term relationships between study variables. The normalized Cointegrating coefficients are found statistically significant and show a stable and positive relationship between study variables. The short run interactions are similar to the long run relationships. The estimated error correction coefficient indicates that 0.6 percent deviation of the inflation rate from its long run equilibrium level is corrected each period where such correction rate for import is 24 percent. Finally, Granger causality analysis suggests the existence of a unidirectional causality running from Inflation to import.JEL Classification Code:  E31
Keywords: Inflation; Import; Cointegration; VECM; Granger Causality